Psicanalisi come critica dell’economia politica. L’economia libidica del capitalismo contemporaneo - Toffoletto, Edoardo (Metapsychologica - rivista di psicanalisi freudiana, 2024)
Psychoanalysis as a critique of political economy. Libidinal economy of contemporary capitalism. The ambition of this essay is to provide a solid epistemological and methodological foundation to the Freudo-marxist project, who attempted to construct a social theory by exploiting Karl Marx’s critique of political economy and Freudian psychoanalysis. The underlying hypothesis of this work is that – beyond the ideological appropriations of that philosophical tradition – both political economy and psychoanalysis happen to study and analyse aspects of the drives that constitute human psychology. Hence, the first section addresses the question of the relation between work and the theory of civilization through a dialogue between theorists and ideologists of Liberalism and psychoanalytic theory by highlighting the roles played by the mechanisms of sublimation and idealization into any working activity. The second section then stresses the insufficient approach of DSM-5 in dealing with critical pathologies, which reveal themselves as none other than symptoms of late capitalism. The notion of depressive hedonia adopted by Mark Fisher to describe his student’s relation to consumerism has been exploited as the entry point to understand the libidinal economy of late capitalism, as well as its normative libidinal type. In the last section, the Freudian analogy between obsessional neurosis and religion is clarified in order to distinguish the traditional religious phenomenon from an understanding of capitalism as religion, which – following Walter Benjamin – consists in a pure cult without dogma. The paper concludes with methodological and epistemological remarks on the possibility to apply psychoanalysis to analyse what Freud calls social neurosis, i.e., on the possibility to use psychoanalysis for the critique of political economy’s ideology.